Modelo criptográfico baseado em autômatos celulares tridimensionais híbridos - Lima, Danielli Araújo (2016)
The popularization of electronic devices to capture digital images, as well as the creation of several applications enabling exchange and sharing these images by communication channels has brought some inherent problems. Among these problems it can be cited the security violation and privacy in information systems. The use of cryptographic systems in such information transmission is required to solve these issues. The main goal of cryptography is to guarantee that the information will not be copied, modied or falsied. Many classic and modern encryption algorithms have been investigated to ensure secure exchange of information. However, when the message to be sent is an image, the conventional algorithms do not favor image structural features: the spatial arrangement and the massive amount of information. Thus, a new approach for this topic is the usage of cellular automata (CA) in image encryption. CA are being studied due to their implementation simplicity and also due to their capacity to process data in a fast parallel way. In this work a novel cryptographic model based on three-dimensional hybrid cellular automata was elaborated and named 3DHCA. This method employs pre-image calculus which represents CA backward evolution and two rules are used in the encryption process. The rst one is called major rule, and it is responsible for the eective encryption of the message. The second one is used only in boundary lattice cells to ensure the existence of pre-image for any lattice. This three-dimensional model is based on a precursor model called HCA, which uses one-dimensional CA. Initially, an analysis of one-dimensional model safety was performed using Graph Theory. The denition of the new three-dimensional cryptographic model, as well as experiments for its validation and renement are discussed in this dissertation. The resulting method has proved to be safe and appropriated for an implementation with a high-level of parallelism. Thus, it becomes a very interesting option for encryption using large volumes of data, especially digital color images.